2019
DOI: 10.3389/fmicb.2019.02300
|View full text |Cite
|
Sign up to set email alerts
|

Use of Wine and Dairy Yeasts as Single Starter Cultures for Flavor Compound Modification in Fish Sauce Fermentation

Abstract: Effects of wine and dairy yeast fermentation on chemical constituents of tilapia fish head hydrolysate supplemented with glucose in an unsalted and acidic environment were investigated. Three wine yeasts (Torulaspora delbrueckii Biodiva, Saccharomyces cerevisiae Lalvin EC-1118 and Pichia kluyveri Frootzen) and one dairy yeast (Kluyveromyces marxianus NCYC1425) were employed as single starter cultures, respectively, and were compared with one soy sauce yeast (Candida versatilis NCYC1433). Each yeast showed diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…As has been shown previously, the optimum incubation time for maximum citric acid production varies with the microbes and fermentation conditions. The optimum citric acid production by S. cerevisiae and C. guilliermondii was attained after 3-5 days of incubation [34], 40 h for Candida lipolytica [35], 12 days for Yarrowia lipolytica [8,10], while using of P. kluyveri to enhance the flavor of fish sauce, it produced citric acid, malic acid, and succinic acid within the first 3 days of fermentation [36].…”
Section: Effects Of Time Course On Citric Acid Productionmentioning
confidence: 97%
“…As has been shown previously, the optimum incubation time for maximum citric acid production varies with the microbes and fermentation conditions. The optimum citric acid production by S. cerevisiae and C. guilliermondii was attained after 3-5 days of incubation [34], 40 h for Candida lipolytica [35], 12 days for Yarrowia lipolytica [8,10], while using of P. kluyveri to enhance the flavor of fish sauce, it produced citric acid, malic acid, and succinic acid within the first 3 days of fermentation [36].…”
Section: Effects Of Time Course On Citric Acid Productionmentioning
confidence: 97%
“…cerevisiae produced more ethyl ester in wine than S. cerevisiae did. These differences in producing abilities of ethyl ester among different yeast strains might be caused by their different producing ability of organic acids, because the organic acids were the precursors of ethyl esters [56]. Among the ethyl ester compounds, ethyl caproate, ethyl octanoate and ethyl caprate were the odor active compounds, which were characterized by "pineapple, fruity and floral", "fruity, pineapple, pear and floral", and "fruity and fresh", respectively (Table 3).…”
Section: Estersmentioning
confidence: 99%
“…The addition of both starter cultures in sequential order showed the potential to improve quality in terms of volatile compounds, glutamic acid content, and overall acceptability with a reduced level of biogenic amine content in the final product (ibid). Recently, it was reported that compared with spontaneous fermentation, products inoculated with starter cultures not only had the typical characteristics of fish sauce, but had better flavor and product quality in saltless (Gao et al., 2019) and low‐salt (3–6%, w/v) fish sauce (Bao et al., 2018; Zang et al., 2020; Zeng et al., 2017).…”
Section: Introductionmentioning
confidence: 99%